Spatial distribution of conduction disorders during sinus rhythm. (15th December 2017) - Lanters, Eva A.H.; Yaksh, Ameeta; Teuwen, Christophe P.; van der Does, Lisette J.M.E.; Kik, Charles; Knops, Paul; van Marion, Denise M.S.; Brundel, Bianca J.J.M.; Bogers, Ad J.J.C.; Allessie, Maurits A.; de Groot, Natasja M.S.
Abstract: Background: Length of lines of conduction block (CB) during sinus rhythm (SR) at Bachmann's bundle (BB) is associated with atrial fibrillation (AF). However, it is unknown whether extensiveness of CB at BB represents CB elsewhere in the atria. We aim to investigate during SR 1) the spatial distribution and extensiveness of CB 2) whether there is a predilection site for CB and 3) the association between CB and incidence of post-operative AF. Methods: During SR, epicardial mapping of the right atrium (RA), BB and left atrium was performed in 209 patients with coronary artery disease. The amount of conduction delay (CD, Δlocal activation time ≥ 7 ms) and CB (Δ ≥ 12 ms) was quantified as % of the mapping area. Atrial regions were compared to identify potential predilection sites for CD/CB. Correlations between CD/CB and clinical characteristics were tested. Results: Areas with CD or CB were present in all patients, overall prevalence was respectively 1.4(0.2–4.0) % and 1.3(0.1–4.3) %. Extensiveness and spatial distribution of CD/CB varied considerably, however occurred mainly at the superior intercaval RA. Of all clinicalcharacteristics, CD/CB only correlated weakly with age and diabetes ( P  < 0.05). A 1% increase in CD or CB caused a 1.1–1.5ms prolongation of the activation time ( P  < 0.001). There was no correlation between CD/CB and post-operative AF. Conclusion: CD/CB during SR in CABG patients with electrically non-remodeled atria show considerable intra-atrial, but also inter-individual variation. Despite these differences, a predilection site is present at the superior intercaval RA. Extensiveness of CB at the superior intercaval RA or BB does not reflect CB elsewhere in the atria and is not associated with post-operative AF.